A conceptual framework for mixing structures in individual aerosol particles. Issue 22 (25th November 2016) - Li, Weijun; Sun, Jiaxing; Xu, Liang; Shi, Zongbo; Riemer, Nicole; Sun, Yele; Fu, Pingqing; Zhang, Jianchao; Lin, Yangting; Wang, Xinfeng; Shao, Longyi; Chen, Jianmin; et al.
Abstract: This study investigated the particle size‐ and age‐dependent mixing structures of individual particles in clean and polluted air. Aerosols were classified into eight components: sea salt, mineral dust, fly ash, metal, soot, sulfates, nitrates, and organic matter (OM). Based on our aerosol classification, a particle that consists of two or more aerosol components can be defined as an internally mixed particle. Otherwise, it is considered to be an externally mixed particle. Within the internally mixed particle class, we identified four heterogeneous mixing structures: core‐shell, dumbbell, OM coating, and dispersed OM, as well as one homogeneous‐like mixing structure. Homogeneous‐like mixing mainly occurred in fine particles (<1 µm), while the frequency of heterogeneously mixed particles increased with particle size. Our study demonstrated that particle mixing structures depend on particle size and location and evolve with time. OM‐coating and core‐shell structures are important indicators for particle aging in air as long as they are distant from specific emission sources. Long‐range transported particles tended to have core‐shell and OM‐coating structures. We found that secondary aerosol components (e.g., sulfates, nitrates, and organics) determined particle mixing structures, because their phases change following particle hydration and dehydration under different relative humidities. Once externally mixed particles are transformed into internally mixed particles, they cannot revert to their former state, except when semivolatile aerosol components are involved. Categorizing mixing structures of individual particles is essential for studying their optical and hygroscopic properties and for tracing the development of their physical or chemical properties over time. Key Points: Our study systematically identifies mixing structures within internally mixed particles Particle mixing structures depend on particle size and location and they evolve over time Secondary aerosol formation mainly determined particle mixing structures in this study